The Crisis of Sufistic Tawhid: Seeking the Divine in Spiritual Cyberspace - Zaki, Moh. (Jurusan Aqidah dan Filsafat Islam Universitas Negri Sunan Gunung Djati Bandung, 2024)
Advancements in digital technology have created a new space for individuals to express and practice their spirituality, including searching for God. However, spiritual cyberspace introduces new challenges regarding the authenticity of spiritual experiences, interpretation of religious beliefs, and impact on traditional religious practices. This study analyses how the concept of Sufi monotheism (tauhid sufistik) can provide a framework for understanding the complexities of religiosity in the digital age. Using a qualitative approach and literature review, this study explores how digitalization transforms faith paradigms and Sufi practices while also examining how cyberspace serves as both a medium for religious exploration and a potential source of spiritual distortion. The findings indicate that, while cyberspace offers broad access to religious knowledge, it also risks replacing traditional religious authority. Therefore, critical awareness is essential for engaging with spiritual cyberspace to ensure that the essence of tauhid is preserved in digital religiosity.